Theaterical art: a new look on the world and transforming force - Shumakova, Svitlana (My University, 2019)
An attempt is made to comprehend the phenomenon of theatrical art as a transforming force that changes the human world. The author interprets the nature of theatrical art as understood one of the most powerful tools affecting the human soul forming a culture of feelings, gaining new experience and a new outlook on the world.
Keywords: сценічне мистецтво, performing arts; театральне мистецтво, dramatic art